Molly and the Twin Towers : a 9/11 survival story - Fleck, Jessika; Pica, Jane (North Mankato, Minnesota : Stone Arch Books, 2021)
When the Twin Towers fall on September 11, 2001, blocks from her school, twelve-year-old Molly, unable to reach her dads or Gran, must find her seven-year-old sister, Adi, and get her safely home. Includes author's note, glossary, and discussion questions.
3.9
3-6
600L
W
OBOB Elementary 2023-2024.
Keywords: September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Survival -- Juvenile fiction; Sisters -- Juvenile fiction; Gay fathers -- Juvenile fiction; Grandmothers -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; September 11 Terrorist Attacks, 2001 -- Fiction; Survival -- Fiction; Sisters -- Fiction; Gay fathers -- Fiction; Grandmothers -- Fiction; New York (N.Y.) -- Fiction; Historical fiction; LGBTQ+ fiction